Pédagogie du développement intégral et de l’éducation d’Edmund Bojanowski dans la communauté multiculturelle de l’Afrique – bases théoriques et possibilités d’application - Szewczak, Iwona (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
The article deals with Blessed Edmund Bojanowski’s pedagogy of integral development and upbringing of man, built on Christian realism and personalism. Adopting the basic assumptions of Bojanowski’s conception and its anthropological foundations, his understanding of upbringing and of the role of an educator, the author points to the universality of Bojanowski’s proposal. The universal nature of his model manifests itself through its person-centred focus, a dialogical approach to upbringing that is capable of respecting the historical situatedness of actual interpersonal relations. The conception, thanks to its universal character, can be implemented in all places and times, including the multicul[1]tural community of Africa. As clearly outlined by the founder of care centres called ochronka (safe place), upbringing can contribute to shaping attitudes in pupils that enable them to participate in dialogue and in constructing their identity in the axiological contexts of their own cultures. In this way, Bojanowski’s programme perfectly matches the definition of contemporary intercultural pedagogy.